Patrones y tendencias de la producción científica sobre calidad del gasto público en las municipalidades: Una revisión bibliométrica - Chire Cruz, Dina Verónica (2025)
The quality of public spending has gained increasing importance due to its contribution to local development and the efficiency of public service delivery. The objective of this study was to analyze the patterns and trends in scientific production on the quality of public spending in municipalities through a bibliometric analysis of the available literature. The methodology employed was qualitative, exploratory, and descriptive, and exclusively using the Scopus database. Seventy-one scientific publications related to the topic were analyzed, identifying an average annual growth of 5% in research output, with a significant increase starting in 2001. Among the most prominent authors are Rocha, Afonso, Hortas-Rico, and Pascual, while the journals with the highest number of publications were Applied Economics (Taylor & Francis Online), Local Government Studies (Taylor & Francis Online), and Economía Aplicada (University of Zaragoza). The United States, the United Kingdom, and Australia lead scientific production from the social and economic sciences perspectives. Analysis of the thematic map reveals that the most relevant topics are strategic approach, public policies, efficiency, and national development, along with emerging approaches such as the top-down model and multilevel planning. It is concluded that the study of the quality of public spending has reached conceptual maturity, highlighting challenges related to methodological integration and global collaboration. Therefore, it is recommended to include new databases that strengthen the evidence found and to incorporate contemporary approaches in public management.